2015
DOI: 10.1177/0363546514566192
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Microstructural Properties of the Anteromedial and Posterolateral Bundles of the Anterior Cruciate Ligament

Abstract: These insights into native ligament microstructure can be used to assess graft options for ACL reconstruction and optimize surgical reconstruction techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 48 publications
3
59
0
Order By: Relevance
“…Although the relative elongation patterns were similar in the AMB and PLB, differences in relative elongation of the bundles were observed. Previously observed differences in material and microstructural properties of the AMB and PLB during loading may be an adaptation to relative elongation differences observed in this study. These observed differences in relative strain suggest non‐uniform loading of the fibers of the ACL.…”
Section: Discussionsupporting
confidence: 59%
“…Although the relative elongation patterns were similar in the AMB and PLB, differences in relative elongation of the bundles were observed. Previously observed differences in material and microstructural properties of the AMB and PLB during loading may be an adaptation to relative elongation differences observed in this study. These observed differences in relative strain suggest non‐uniform loading of the fibers of the ACL.…”
Section: Discussionsupporting
confidence: 59%
“…For many years the anatomy of the ACL was described to have at least two bundles, the anteromedial and posterolateral one. The division was based on anatomical studies and used for biomechanical models 2,3,24,25 . In an attempt to improve clinical results the latest technique developed was to reconstruct the AM and PL bundles separately in a double bundle technique [26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Gao and Messner () mechanically loaded a range of rabbit knee ligaments, and found that greater frequency and depth of the interdigitations at the bone‐soft tissue interface was positively correlated to the strength of the ligament. Skelley et al (), studying the human ACL showed that the AM bundle was significantly stronger than the PL bundle, but did not include an investigation of the insertions of the respective bundles into bone.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggest that the relatively smooth bone contour and shallow insertion of the PL region of the ACL, closer to the centre and sagittal midline of the joint, reflects its less dominant role in mechanical stabilization. It has been suggested by microstructural property studies that the AM bundle is the primary load bearing region of the ACL with the AM bundle possessing a higher tissue modulus and failure to stress than the PL bundle (Skelley et al, ). The present study reinforces this point, where the difference in insertion morphology between the AM and PL region is consistent with the idea that the AM is more designed for larger loadings than the PL (Benjamin et al, ).…”
Section: Discussionmentioning
confidence: 99%